Masa Tua Tanpa Derita: Peningkatan Kualitas Hidup Lansia Panti Werdha Damai Ranomuut Bermetode Audio Therapy Terintegrasi Afirmasi Positif dalam Manajemen Stres: Penelitian - Cliford Rafael Kevin Kindangen; Tineke Marlyn Langi; Solideo Bernad Dajoh; Kezia Juanita Makalow; Amazingrace Zefania Gloria Suwuhang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The quality of life for the elderly has generally not yet reached optimal levels. The aging process is a phase that provides fewer positive stimuli, potentially decreasing the quality of life for the elderly. This is characterized by dissatisfaction with life and low stress management skills. This condition is experienced by the elderly living in nursing homes due to inadequate quality of life. This program is a stress management program that uses audio therapy to improve quality of life, conducted in partnership with the elderly at the Damai Ranomuut Nursing Home. This program aims to reconstruct the mindset of the elderly in a positive direction with the support of enjoyable activities. The method used is therapy with audio loaded with positive affirmations according to the preferences of the elderly. The application of this method increased the quality of life score from 13.4 to 31.2, according to the Satisfaction With Life Scale (SWLS) test score.